A Review of the Health Act 2017 Using the Availability, Accessibility, Acceptability and Quality Framework - Adionyi, Claire (Strathmore Law Journal, 2020)
The International Covenant on Economic, Social and Cultural Rights (ICESCR) provides for the right to the highest attainable standard of health. Kenya has ratified this Covenant and is, therefore, bound by its provisions. The Constitution of Kenya (2010) further establishes a framework for expanding rights and freedoms under Article 24 (4). The Constitution expressly provides for the right to health under Article 43 (1), which led to the enactment of the Health Act in 2017 (the Act). Article 43 (1) (a) of the Constitution states: 'Every person has the right to the highest attainable standard of health, which includes the right to health care services, including reproductive health care.' On this light, the right to health will be analyzed in the following lines.